Barriers to Student Expression on Mental Health - Aniket Ramasre Gupta; Mohamed Afzal Nandolia (International Journal of Behavioral Sciences, 2025)
It focuses on the challenges faced by students in openly expressing their opinions and emotions regarding mental health, which is an essential yet often sensitive topic. The research, conducted upon 52 students with an age range of 18 to 26, highlights the perceptions students have about mental health and the difficulties they face in seeking help. Even though 78.4% of the respondents emphasized the need for increased mental health awareness, results indicate that stigma, a lack of awareness, cultural norms, and mistrust in mental health support systems still exist. Observations based on gender indicated subtle attitudes with female participants open to discussion, while, by contrast, male participants tried to keep their issues to themselves as matters of social expectations. The article calls for the availability of affordable resources for mental health primarily in academic settings, thus bridging the gap between awareness and action. Recommendations would include the implementation of stigma-reduction programs, design of safe discourse spaces, and promotion of targeted therapies such as workshops, peer support groups, and confidential counseling services. It aims to educate educators, mental health professionals, and legislators on the need for a culture to normalize discussing mental health topics. This can allow kids to seek out treatment without fear of judgment. By eliminating these impediments, academic institutions can help in overall well-being and achievement of students.
Keywords: Stigma and Cultural Norms; Student Perceptions; mental health awareness